If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6v + -1(1 + 8v) = -113 -6v + (1 * -1 + 8v * -1) = -113 -6v + (-1 + -8v) = -113 Reorder the terms: -1 + -6v + -8v = -113 Combine like terms: -6v + -8v = -14v -1 + -14v = -113 Solving -1 + -14v = -113 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -14v = -113 + 1 Combine like terms: -1 + 1 = 0 0 + -14v = -113 + 1 -14v = -113 + 1 Combine like terms: -113 + 1 = -112 -14v = -112 Divide each side by '-14'. v = 8 Simplifying v = 8
| 3x-3=3[7-x] | | 27+4+61=14x+8 | | 0.15-0.01(x+1)=0.02(2-x) | | 7x-(-1)=-4 | | 500x+x^2=1000 | | 295+39n=350+33n | | 9.2x-8.8= | | 4(x+5)-2x=22 | | 5.00+.75x=6x | | for((5.6)(5.6))+((12)(12))=((c)(c)) | | .75(6j+9)=3j+7 | | -3n-4+n=2 | | (18X+27)(X^4+6x^3+9x^2)=0 | | 24=2l | | 12c+6c=39 | | 7x(-5)=-25 | | 5+.75m=6m | | 2x+20+x= | | -15x+2(4x-7)=-16-6x | | 159+20x-1=59x+2 | | 5(3x-1)+5=-60 | | 5x=5(-4+3x) | | 0=125+5.2t-4.9t^2 | | 6(-1-7r)=-6-r | | 6x-x=5x+30 | | SOLVEforlP=2l+2w | | 7x+4q=5 | | -6x+2(x-3)=30+2x | | (x+5)2-1=0 | | 7x-5=-25 | | -4.8x-0.12= | | 15x-3=y |